Meningkatkan Kemampuan Fisik Motorik Halus Anak Kelompok B Melalui Metode Demonstrasi - nurhayati nurhayati; Bastiana Bastiana; Ramlah Ramlah (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine students' level of success in the Physical Fine Motor aspects through the Demonstration Method. The approach used is a qualitative approach where research is based on descriptive data from spoken words or observable behavior. Demonstration assessment techniques can be carried out using a checklist and rating scale. This research was conducted at Kemala Bhayangkari Kindergarten with ten students. Applying the demonstration method by making cow puppets can improve children's fine motor development, which previously only 30% of children's achievement levels increased to 90%.